Phosphonic acid mediated practical dehalogenation and benzylation with benzyl halides. Issue 39 (18th July 2019) - Xiao, Jing; Ma, Yonghao; Wu, Xiaofang; Gao, Jing; Tang, Zilong; Han, Li-Biao
Abstract : A practical method for phosphonic acid mediated dehalogenation and benzylation with benzyl halides was developed. Abstract : For the first time, by using H3 PO3 /I2 system, various benzyl chlorides, bromides and iodides were dehalogenated successfully. In the presence of H3 PO3, benzyl halides underwent electrophilic substitution reactions with electron-rich arenes, leading to a broad range of diarylmethanes in good yields. These transformations feature green, cheap reducing reagents and metal-free conditions. A possible mechanism was proposed.